The Application of an Edible Coating with Yellow Pumpkin Extract to Fresh Chicken Meat and its Physical Quality are reviewed - Wiryawan, Dimas; Manab, Abdul; Susilo, Agus (Jurnal Ilmu-Ilmu Peternakan, 2025)
An edible coating made from whey protein isolate-chitosan with yellow pumpkin extract can maintain the physical quality of fresh chicken meat. This study aimed to determine the physical characteristics of fresh chicken meat by applying an edible coating made from whey protein isolate-chitosan with yellow pumpkin extract. This study uses a random group design with nesting patterns. The first factor is the coating (C) and uncoated (NC) edible coating, and the second factor is the length of meat storage, namely, day 0 (D0), day 2 (D1), day 4 (D2), and day 6 (D3). The data tested were pH, texture, WHC, cooking loss, moisture content, and color. The data were collected and analysed via Microsoft Excel. The results revealed a significant difference in the pH value (P < 0.01). The pH ranged from 4.97–6.32. The color and cooking loss values were significantly different (P < 0.05), with values ranging from L*(33.9–56.7), a*(-3.36–4.21), b*(4.25–12.1), WI (32.64–55.79), C*(2.28–50.63) and h? (70.75–111.5), while the cooking loss ranged from 25.28–38.55%. The moisture content, texture, and WHC values were not significantly different (P > 0.05), with moisture contents ranging from 70.16–74.30%, textures ranging from 3.85–5.85 N, and WHCs ranging from 24.55–37.66%. An edible coating yields good results on meat stored for up to the sixth day, whereas meat not stored with the coating has poor quality on the sixth day.